If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2(3n + -2) + 4n = 0 Reorder the terms: 5 + -2(-2 + 3n) + 4n = 0 5 + (-2 * -2 + 3n * -2) + 4n = 0 5 + (4 + -6n) + 4n = 0 Combine like terms: 5 + 4 = 9 9 + -6n + 4n = 0 Combine like terms: -6n + 4n = -2n 9 + -2n = 0 Solving 9 + -2n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2n = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2n = 0 + -9 -2n = 0 + -9 Combine like terms: 0 + -9 = -9 -2n = -9 Divide each side by '-2'. n = 4.5 Simplifying n = 4.5
| 8m+16=20+8m | | X+(-11.64)=-6.96 | | 9(m-2)-2m+3= | | 2x-19=3x+22 | | 75a^4b-3a^2b=0 | | -12.1+16.4+x=-3.7 | | 2x-9=3x+22 | | 42/3+44/5 | | -8c+6-15c+4= | | -x+3+3+2x=6-7 | | 7x-9y=6 | | 3/4a-3=9 | | 35x^2+31x+6=0 | | 10y+12-20y+5= | | y/3+8y/4-3/6=y+7/2 | | 20-a=3(4-a) | | 3.2d=-4 | | 7(1/7y)=(7)(-3) | | 15+3x-6+2x=21 | | y=-0.90(50)+113 | | -0.06p-0.04(2-4p)=0.05(p-6)-0.23 | | y=-0.90(40)+113 | | 8d+31=3.4d+19 | | 3x-5x+13-9= | | 9x-x+5x=260 | | y=-0.90(30)+113 | | -4-1/3= | | .5x=.4x+9 | | 14x^2-5x+15=2 | | y=-0.90(20)+113 | | 10x+8x-2+3x-5= | | -3/2(-2/3)(2y+4)=(-3/2)8 |